Seismic performance-based design and risk analysis of thermal power plant building with consideration of vertical and mass irregularities. (1st June 2018) - Wang, Jianze; Dai, Kaoshan; Yin, Yexian; Tesfamariam, Solomon
Highlights: A power plant structure with extreme mass and stiffness irregularities are studied. Seismic analyses considering nonlinearity are performed with OpenSees models. Mass and stiffness irregularity effects on fragility and seismic risk are compared. Abstract: Industrial buildings often have irregularities due to operational and complex industrial process. In this paper, a thermal power plant with mass and vertical irregularities was designed with the 2010 ASCE and AISC design codes. Subsequently, a parametric study was undertaken on simplified braced frames to quantify the impact of mass and vertical irregularities, as well as their combined effect. Detailed numerical models were developed in Open System for Earthquake Engineering Simulation platform. With a high seismicity level in China, ground motions were selected and nonlinear time-history analyses were performed. Subsequently, probabilistic seismic demand models, seismic fragilities, and risks were developed for different performance levels. The results show that the vertical irregularity generated larger detrimental effect than mass irregularity, and need more attention in structural design. Collapse risk increased the most due to the combined effect of mass and vertical irregularities. Furthermore, under small earthquake intensities, the thermal power plant with the combined irregularities had higher risk in functional disruption.